The order of normal form generalized hypersubstitutions of type τ = (2) - Sudsanit,S. (Kyungpook National University, 2015)
In 2000, K. Denecke and K. Mahdavi showed that there are many idempotent elements in HypNϕ(V ) the set of normal form hypersubstitutions of type τ = (2) which are not idempotent elements in Hyp(2) the set of all hypersubstitutions of type τ = (2). They considered in which varieties, idempotent elements of Hyp(2) are idempotent elements of HypNϕ(V ). In this paper, we study the similar problems on the set of all generalized hypersubstitutions of type τ = (2) and the set of all normal form generalized hypersubstitutions of type τ = (2) and determine the order of normal form generalized hypersubstitutions of type τ = (2).